Computer networks and internets : with Internet applications - Comer, Douglas. 4 0 16; 5 (Upper Saddle River, NJ : Pearson/Prentice Hall, 2004)
An introduction to computer networks and the internet applications they provide that provides an overview of key topics, practice exercises, and detailed descriptions and instructions.
Includes bibliographical references (p. [693]-700) and index.
Adult;Adult
System requirements stated.
Keywords: 2 -- 0; 6; Computer networks.;Internetworking (Telecommunication). -- 20; 20; CD-ROMs.